Patogenisitas Colletotrichum musae Penyebab Penyakit Antraknosa Pada Beberapa Varietas Buah Pisang - Wilhemina Rumahlewang; Handry R.D Amanupunyo (Faculty of Agriculture, Pattimura University, 2012)
Low quality of banana fruits due to anthracnose caused by Colletotrichum musae fungi could be overcome by introducing anthracnose-resistent varieties. The research’s objective was to find out pathogenecity of C. musae on six local banana varieties namely Dewaka, Ambon Kuning, Abu-abu, Raja, Empat Puluh Hari and Nona. A laboratory experiment was carried out by using completely randomized block design with six replicates. The result showed that the pathogenicity of C. musae on six varieties of banana fruits was differ. Average incubation period of fungi and damage level of banana fruits were 3.5 days and 32.53% respectively whereas average rate of infection of C.musae was 0.115 units/day. This experiment suggested that banana var. Abu-abu was resistance to anhtracnose while banana var. Raja, Ambon Kuning as well as Dewaka were susceptible to anthracnose. Banana var. Empat Puluh hari and Nona were classified in moderately resistance to anthracnose.